2014
DOI: 10.1155/2014/957145
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effects in a Lake Sediment Archaeal Community of the Brazilian Savanna

Abstract: The Cerrado is a biome that corresponds to 24% of Brazil's territory. Only recently microbial communities of this biome have been investigated. Here we describe for the first time the diversity of archaeal communities from freshwater lake sediments of the Cerrado in the dry season and in the transition period between the dry and rainy seasons, when the first rains occur. Gene libraries were constructed, using Archaea-specific primers for the 16S rRNA and amoA genes. Analysis revealed marked differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 63 publications
1
15
0
13
Order By: Relevance
“…Few previous studies indicated the variation of archaeal community diversity with sediment depth and sampling site Lucheta et al 2013). Rodrigues et al (2014) suggested the seasonal effects on archaeal community diversity in lake sediment of the Brazilian Savanna. Lake sediment archaeal community structure could be influenced by pollution (Haller et al 2011), sediment depth (Borrel et al 2012;Mandic-Mulec et al 2012), and salinity (Jiang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies indicated the variation of archaeal community diversity with sediment depth and sampling site Lucheta et al 2013). Rodrigues et al (2014) suggested the seasonal effects on archaeal community diversity in lake sediment of the Brazilian Savanna. Lake sediment archaeal community structure could be influenced by pollution (Haller et al 2011), sediment depth (Borrel et al 2012;Mandic-Mulec et al 2012), and salinity (Jiang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Vale ressaltar que embora efeitos imediatos das queimadas nas propriedades e composição dos solos tenham sido relatados na literatura, principalmente relacionados ao aumento temporário de pH gerado pela deposição de cinzas resultantes da vegetação queimada e a mobilização de nutrientes estocados na biomassa viva e serapilheira para o solo (Pivello & Coutinho, 1992;Miranda et al, 2004;Pivello et al, 2010) (Bano et al, 2004;Etto et al, 2012;Hansel et al, 2008;Simister et al, 2012). Trabalhos anteriores de nosso grupo de pesquisa também empregaram esse par de iniciadores e demonstraram sua eficiência na descrição de membros do domínio Archaea em solos (Catão et al, 2013) e sedimentos lacustres do cerrado (Rodrigues et al, 2014). Desta forma, esse par de iniciadores -21f e 958r -foi escolhido neste trabalho para a descrição da comunidade de archaeas em solos de…”
Section: Resultsunclassified
“…Por esse motivo, as archaeas foram então por muito tempo associadas apenas a locais com ausência de oxigênio, altas temperaturas e extremos de pH ou salinidade, fazendo com que esses ambientes fossem alvos de muitos estudos relacionados a membros deste domínio (Darland et al, 1970;Balch et al, 1979;Fiala & Stetter, 1986;Mathrani et al, 1988;Barns et al, 1994;Blochl et al, 1997) Nos anos seguintes, muitos trabalhos relataram e seguem relatando a ampla distribuição das archaeas em diferentes ambientes terrestres e aquáticos mesófilos, assim como em ambientes extremos (Delong, 1998;Chaban et al, 2006). Archaeas já foram detectadas em diversos solos (Bintrim et al, 1997;Sliwinski & Goodman, 2004;Timonen & Bomberg, 2009), lagoas de água doce (Vissers et al, 2009), ecossistemas marinhos (Wuchter et al, 2006;Silveira et al, 2013), sedimentos (Glissman et al, 2003;Rodrigues et al, 2014), estações de tratamento de esgoto (Gray et al, 2002) e até em diversas partes do corpo humano (Eckburg et al, 2003;Horz & Conrads, 2010;, entre outros ambientes. Hoje em dia, considera-se que a distribuição de archaeas no ambiente seja equivalente à bacteriana.…”
Section: Ubiquidade De Archaeaunclassified
See 1 more Smart Citation
“…(Cowie et al, 2011) até canais poluídos no Egito (Elsaied, 2014). Além disso, trabalhos realizados por nosso grupo utilizaram com sucesso esse par de iniciadores em estudos de caracterização filogenética de amostras de solo (Catão et al, 2013) e de sedimentos lacustres do Cerrado (Rodrigues et al, 2014).…”
Section: Microscopia De Força Atômica -Mfaunclassified